Development of a Droplet Digital Polymerase Chain Reaction for Sensitive Detection of Pneumocystis jirovecii in Respiratory Tract Specimens - Yi, Jie; Wang, Nan; Wu, Jie; Tang, Yueming; Zhang, Jingjia; Zhu, Lingxiang; Rui, Xiao; Guo, Yong; Xu, Yingchun (Frontiers in Medicine, 2021)
Background: Pneumocystis jirovecii pneumonia (PJP) is a life-threatening opportunistic lung infection that affects immunocompromised patients. Moreover, Pneumocystis jirovecii (PJ) colonization may be linked to the development or transmission of PJP. The detection of PJ in immunocompromised patients is thus especially important. The low fungal load and the presence of PCR inhibitors limit the usefulness of quantitative PCR (qPCR) for accurate absolute quantification of PJ in specimens. Droplet digital PCR (ddPCR), however, presents a methodology that allows higher sensitivity and accuracy. Here, we developed a ddPCR method for detecting PJ DNA in respiratory specimens, and evaluated its sensitivity against qPCR. Materials and methods:One bronchoalveolar fluid (BALF) sample each was collected from 82 patients with potential PJP to test the presence of PJ DNA using both ddPCR and qPCR, and samples with inconsistent results between the two methods were further tested by metagenomic next generation sequencing (mNGS). In addition, 37 sputum samples from 16 patients with diagnosed PJP, as well as continuous respiratory tract specimens from 9 patients with diagnosed PJP and treated with sulfonamides, were also collected for PJ DNA testing using both ddPCR and qPCR. Results: ddPCR and qPCR gave the same results for 95.12% (78/82) of the BALF samples. The remaining 4 specimens tested positive using ddPCR but negative using qPCR, and they were found to be positive by mNGS. Detection results of 78.37% (29/37) sputum samples were consistent between ddPCR and qPCR, while the other 8 samples tested positive using ddPCR but negative using qPCR. The PJ load of patients with PJP decreased after treatment according to qPCR, even to undetectable levels, but PJ was still detectable using ddPCR. Conclusions: ddPCR was more sensitive than qPCR, especially at detection low-pathogen-load PJ. Thus, ddPCR represents a useful, viable, and reliable alternative to qPCR in PJ testing in patients with immunologic deficiency.